While we run - Healey, Karen. (Little, Brown and Company, 2014)
"It's the year 2128, and Tegan Oglietti, the world's first successfully revived cryonics patient, and her maybe-boyfriend, Abdi Taalib, are on the run from the government and from a dangerous rebel group. When they uncover shocking new information about the cryonics program, they are faced with an impossible decision that will put thousands of lives in their hands"--